Eksplorasi serta Isolasi Trichoderma sp. sebagai Agen Hayati pada Lahan Budidaya Blewah di Semolowaru, Surabaya - Andriani, Vivin; Purity Sabila Ajiningrum (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2026)
This study aimed to analyze the effect of shiitake mushroom (Lentinula edodes) flour substitution on the content of vitamin C, vitamin D, and folate in cookies as a functional food product. A single-factor experimental design using a Completely Randomized Design (CRD) was applied with five levels of shiitake flour substitution (0%, 7.5%, 15%, 22.5%, and 30%), each conducted in five replications. The results demonstrated that the contents of vitamin C, vitamin D, and folate increased progressively with higher levels of shiitake flour substitution. Statistical analysis revealed that the increases in vitamin C, vitamin D, and folate were significant (p<0.05) across all treatment levels, with the highest values observed at 30% substitution. This trend indicates that shiitake flour serves as an effective natural source of micronutrients, particularly vitamin C, vitamin D, and folate. Therefore, cookies formulated with 30% shiitake flour substitution can be recommended as a functional food with the potential to enhance the intake of essential micronutrients, especially for pregnant women.   Keywords : Shiitake mushroom; functional food; vitamin C, vitamin D; folate